The Relationship Organizational Culture and Organizational Commitment on Public Service Quality; Perspective Local Government in Bandung, Indonesia - Hadian, Dedi (International Review of Management and Marketing, 2017)
Literature studies prove the importance the role of organizational culture and organizational commitment that contribute to organizational performance, but it is a few links to the quality of public services. This study was conducted to contribute in cultural studies' organizations and organizational commitment to public service. The research object of government organizations in the city of Bandung, Indonesia with a sample of 187 employees with proporsionate cluster random sampling technique. Data were analyzed using Structural Equation Modeling (SEM) Partial Least Squares. The results showed that organizational culture and organizational commitment significantly influence the quality of public services. This suggests that policy makers in Bandung local goverment, Indonesia should be able to improve organizational culture and organizational commitment to public service that is accepted by society can run optimally. Keywords: organizational culture, organizational commitment, public service quality. JEL Classifications: H83, M14, M38